Questions of the Narrators and the Interpretive Answers of Imam Al-Sadiq (Peace Be Upon Him) - Mahal, Nour Al-Huda Hussein; Shamam, Prof.Dr. Fatima Kazem (South Eastern European Journal of Public Health, 2024)
The narrations received from Imam Al-Sadiq (peace be upon him) contribute to explaining and clarifying many interpretative rulings that are an important source for understanding many of the doctrinal rulings related to the oneness of Allah and the answers of Imam Al-Sadiq (peace be upon him), it is necessary to stand on these narrations and study their support and indicate the conditions of their narrations in terms of strength and weakness and by referring to the and the answers of Imam Sadiq (peace be upon him) about these questions, and then I came to a conclusion that includes the most important The results I came up with.